Dodecanese Islands in Diplomatic Struggle during the Period of Italian Neutrality in WWI (1914-1915) - T. P. Nesterova (Научный диалог, 2018)
The history of the Italian diplomatic struggle for recognition of the Italian control over the Dodecanese Islands during the period of Italian neutrality during the First world war is considered. The archipelago, captured by Italy during the Libyan war of 1911-1912, was of great strategic importance as a natural centre for establishing a sphere of influence in the Eastern Mediterranean. Italy de facto refused to implement the provisions of international treaties providing for the evacuation of Italian occupation forces from the archipelago. The article proves that during the First world war, especially during the period of Italian neutrality (1914-1915), each of the opposing sides - the Entente (France, Great Britain, Russia) and the Central powers (Germany and Austria-Hungary) - sought Italy’s entry into the war on their side, using the issue of the Dodecanese Islands to strengthen Italy’s interest in participating in the war. At the same time, Greece, which the great powers also sought to bring to participate in the war, also sought to establish its own control over the Islands of the archipelago. In a situation where Germany and Austria-Hungary could not oppose the interests of their ally - the Ottoman Empire, for France and Britain the decisive question was which country they were more interested in attracting to participate in the war - Italy or Greece. As a result, Italy chose to go to war on the side of the Entente, because the territorial concessions offered by the Entente countries to Italy were much more significant than the proposals of Germany and Austria-Hungary. The Dodecanese Islands remained a bargaining chip in the great diplomatic game.